2021
DOI: 10.3390/polym13223900
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions of Polarised PVDF Films in a Standard Curing Process for Composites

Abstract: The article reports on the influence of annealing PVDF in an autoclave process on the PVDF phase composition. DSC, FTIR and XRD measurements serve to observe the phase changes in an already stretched, polarised and β-phase rich film. Annealing was conducted between 90 and 185 ∘C to cover a broad range of curing processes in an autoclave. The β-phase is found to be stable up to near the melting range at 170 ∘C. At 175 ∘C, the non-piezoelectric α-phase dominates and the piezoelectric γ- and γ′-phases appear. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…The suitable addition of 5CB induces heterogeneous nucleation and accelerates the nucleation process, resulting in an increment in the T c value and the degree of crystallinity. 48 It has been reported that the increment of the crystallinity contributes to the enhanced mechanical strength and dielectric insulation performance (such as E b and lifetime). 49 However, 5CB acts as a diluent to hinder the crystallization process and reduce T c when 5CB is over a certain amount.…”
Section: Resultsmentioning
confidence: 99%
“…The suitable addition of 5CB induces heterogeneous nucleation and accelerates the nucleation process, resulting in an increment in the T c value and the degree of crystallinity. 48 It has been reported that the increment of the crystallinity contributes to the enhanced mechanical strength and dielectric insulation performance (such as E b and lifetime). 49 However, 5CB acts as a diluent to hinder the crystallization process and reduce T c when 5CB is over a certain amount.…”
Section: Resultsmentioning
confidence: 99%
“…XRD measurements were utilized to examine the crystalline phases of these prepared PVDF-HFP-matrix electrolyte films, and the resulting XRD diffraction patterns are present in Figure a. The untreated PVDF-HFP-F electrolyte film shows the broadening peak between 18 and 20°, indicating the well-known semicrystalline behavior and a combination of crystalline phases α, β, and γ of PVDF . In particular, the diffraction peaks at 18.4°, and 19.9° represent the (020) and (110) crystalline planes of the α phase, while the peak at 20.3° stands for the (101) crystalline plane of the γ phase, and the peak at 20.7° illustrates the (110), (200) crystalline planes of the β phase, respectively .…”
Section: Resultsmentioning
confidence: 99%
“…The dielectric, ferroelectric, and piezoelectric properties are enhanced by the conformations with a larger dipole moment, i.e., in the electroactive phases β and γ. The phase composition was observed to be sensitive to the processing strategy and parameters, to co-polymerisation [ 41 , 42 ], or by nanofiller additions [ 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%